SALURAN PEMASARAN KOPI ROBUSTA (Coffea robusta) DI AGROFORESTRI PEKON AIR KUBANG, KECAMATAN AIR NANINGAN, KABUPATEN TANGGAMUS - Annisa Marchantia Pratiwi; Hari Kaskoyo; Susni Herwanti; Rommy Qurniati (Forestry Study Program University Of Mataram, 2019)
Agroforestry systems, with products in the form of robusta coffee, can increase income and environmental sustainability. The research objective is to find out the robusta coffee marketing channel. Retrieval of data through interviews with actors or institutions involved, observation, and documentation studies. The data obtained were analyzed descriptively qualitatively about the structure, behavior, and market channels. The results of the study indicate that there are several marketing institutions, namely: farmers, collectors, wholesalers, retailers, and cooperatives. In addition, there are three channels of robusta coffee marketing, namely: (1) farmers to collectors, then wholesalers and retailers, (2) farmers to cooperatives, then retailers, and (3) farmers to cooperatives. The most efficient channel is the third channel, but most farmers choose to sell their coffee to the first channel. This is because of the closer distance to the collecting traders, the lending of money given to farmers by collecting traders, and the absence of special treatment for coffee sold. The market structure formed in coffee marketing is the oligopsonist market, where the price of coffee is determined by large traders. The capacity of cooperatives should be improved by the government in order to compete with collectors, wholesalers, and retailers.